Soluble ST2 as a biomarker for predicting severe adverse events among pediatric patients with Mycoplasma pneumoniae pneumonia - Fangying Cheng; Tingting Li; Lei Zhang; Menghua Xu; Luxi Chen; Zhicheng Ye; Jin Xu (PLoS ONE, 2026)
Aim Mycoplasma pneumoniae (MP) is a leading cause of pneumonia in children. Early identification of patients at high risk is critical for improving outcomes. This study aimed to evaluate the association of soluble ST2 (sST2) with in-hospital adverse events in pediatric MP pneumonia (MPP). Methods We retrospectively analyzed 147 children with MPP admitted to the Children’s Hospital of Fudan University, Shanghai, China, between 01/04/2023 and 31/05/2024. Demographic, clinical, and laboratory data were collected, including sST2, inflammatory markers (CRP, PCT, IL-6), and blood cell counts. Severe adverse events were defined as in-hospital death, ICU admission, diagnosis of sepsis or use of extracorporeal membrane oxygenation. Results Twelve patients experienced severe adverse events and had significantly higher sST2 levels. ROC analysis showed that sST2 predicted severe adverse events (AUC = 0.944, 95% CI 0.894–0.975, P < 0.001), with an optimal cut-off of 114.18 ng/mL (sensitivity 91.7%, specificity 94.8%). The association remained significant after adjusting for age, sex, PCT, and IL-6. In addition, admission sST2 levels were significantly higher in severe MPP cases, those with co-infections and those with pulmonary complications and/or extrapulmonary complications during hospitalization. sST2 correlated positively with hospital length of stay and preadmission fever duration. They also correlated positively with neutrophil counts, neutrophil to lymphocyte ratio, PCT, CRP and IL-6 but negatively with lymphocyte counts. Conclusions. sST2 was associated with in-hospital adverse events and it showed better performance in predicting severe adverse events than other inflammatory biomarkers. The potential of sST2 as a prognostic biomarker for MPP warrants further investigation.